Expansion of the Economic Cooperation of Belarus with SCO - E. Dostanko (Международная аналитика)
The author considers the economics as the most perspective field of cooperation of Belarus and SCO countries. The cases of concrete projects successfully launched in Belarus together with member countries of SCO are demonstrated, as well as proposals for Belarus participation in the project of Silk Road Economic belt. Main indices of Belarus economic growth are presented. The country is interested in Eurasian integration from economical point of view. At the same time the country seeks cooperation with EU on socio-cultural preconditions, Foreign policy priorities are China and Kazakhstan. Belarus is interested in upgrading its level of participation in SCO and becoming an observer state.